2021
DOI: 10.2196/25838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a School-Based Physical Activity Intervention for Obesity and Health-Related Physical Fitness in Adolescents With Intellectual Disability: Protocol for a Randomized Controlled Trial

Abstract: Background Childhood obesity accompanied by lower levels of health-related physical fitness (HRPF) is a major threat to public health both internationally and locally. Children with intellectual disability, especially adolescents, have a higher risk of being overweight/obese and having poor HRPF levels. Therefore, more interventions are needed to help this population attain their optimal health levels. However, there has been relatively limited research on this population compared with on their typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Youths with IDs in the present study were discovered to have significant improvements in physical fitness components, namely cardiorespiratory fitness and abdominal strength and endurance, after the 12-week floor hockey intervention ( Table 4 and Figure 2 ). Findings accord with several intervention studies on youths with IDs and typically developing youths that have revealed positive effects of PA interventions on several physical fitness outcomes in this population [ 13 , 37 , 38 , 60 , 63 , 64 ]. These improvements in the physical fitness of the participants with IDs may be attributable to improvements in motor proficiency due to increases in PA (i.e., floor hockey training).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Youths with IDs in the present study were discovered to have significant improvements in physical fitness components, namely cardiorespiratory fitness and abdominal strength and endurance, after the 12-week floor hockey intervention ( Table 4 and Figure 2 ). Findings accord with several intervention studies on youths with IDs and typically developing youths that have revealed positive effects of PA interventions on several physical fitness outcomes in this population [ 13 , 37 , 38 , 60 , 63 , 64 ]. These improvements in the physical fitness of the participants with IDs may be attributable to improvements in motor proficiency due to increases in PA (i.e., floor hockey training).…”
Section: Discussionsupporting
confidence: 86%
“…Two studies conducted in Asia on samples of more than 400 youths with IDs identified significant correlations of motor proficiency with muscular strength and endurance and cardiorespiratory fitness [ 65 , 66 ]. The positive findings of the current study echo those of early studies [ 13 , 37 , 38 , 60 , 63 ], synthesizing evidence regarding the effects of PA training on physical fitness levels in youths with IDs. Our results also extend the findings of these early studies by indicating that floor hockey practice can improve not only physical fitness but also other motor proficiency and adaptive functioning outcomes among youths with IDs.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations